Assessment of percutaneous transhepatic portal vein embolization with portal vein stenting for perihilar cholangiocarcinoma with severe portal vein stenosis. (25th December 2014) - Hyodo, Ryota; Suzuki, Kojiro; Ebata, Tomoki; Komada, Tomohiro; Mori, Yoshine; Yokoyama, Yukihiro; Igami, Tsuyoshi; Sugawara, Gen; Naganawa, Shinji; Nagino, Masato
Abstract: Background: The aim of the present study was to assess the clinical efficiency of portal vein (PV) stenting when performed with preoperative percutaneous transhepatic portal vein embolization (PTPVE) in patients with severe PV stenosis due to tumor invasion. Methods: Between 2007 and 2013, four consecutive patients (one male, three females; mean age, 52 years; age range, 25–73 years) with perihilar cholangiocarcinoma and PV stenosis underwent PTPVE and PV stenting. Patients were analyzed with regard to the procedure, hypertrophy of the future remnant liver (FRL), and plasma clearance rate of indocyanine green by the FRL (ICGK‐F). Further, the %FRL volume increase in PTPVE was compared between the stenting group and the usual PTPVE group who have perihilar cholangiocarcinomas without PV stenosis. Results: Preoperative PTPVE with PV stenting was successfully performed and portal flow to the FRL improved after stenting in all four patients. The %FRL volume increase was 18–60% (mean, 34%) in the stenting group and was 12–51% (mean, 21%) in the usual PTPVE group. The ICGK‐F value after PTPVE exceeded 0.05 in all four patients. All patients achieved R0 resection. Conclusions: Preoperative PTPVE with PV stenting appears to be feasible in cases of severe PV tumor invasion and stenosis. This procedure may allow a broader indication for surgery.